The Evaluation of Bank Efficiency in Post Merger Stage in Banking Industry - Rahmat Siauwijaya (Binus Business Review, 2017)
This research evaluated the technical efficiency of the banks before and after the merger. This research observed 15 banks which involve in merger activities. This research used the Data Envelopment Analysis (DEA) method with variables of returns to scale (VRS) and input orientation. Analysis of variance (ANOVA) was also applied to test the difference between the technical efficiency in pre- and post-merger activities. This research finds that only six banks are efficient after the merger. Furthermore, four banks have a better technical efficiency than before, andfive banks have lower technical efficiency after the merger.